Pembacaan Ulang Terhadap Imamah Sholat Perempuan - Najwah, Nurun (Musawa Jurnal Studi Gender dan Islam, 2008)
The debates over the degree of authority belong to women have been heavily developed on the ground of religious discourse. One of the most ctusial points is the leadership of women in mixed congregation where women and men are aprticipating in the prayers. The majority of Muslim scholars consider that women leadership in mixed congregation is out of question of contextulization reasoning of religious precept. On the one hand, the presence of Muhammad as the Prophet who conveyed the divine revelation has been seen as improving the status of women and their space as so equal to men as shoum clearly in surat An-Niso' (4): 124. On the other hand, however, there are also verses that claimed by scholars, which reduce women's rights, and there are also scholars who have denied women's access and rights to compete with men in good deeds (fastabiqul khairat). This article is specifically addressing and arguing for reinterpreting the right of women to lead mixed congregated prayers by ways of integrating dialectic discourse of Qur'anic verses and prophetic examplary actions.